Cognitive HF radar. Issue 20 (18th September 2019) - Anderson, Stuart
Abstract : Radars operating in the high‐frequency (HF) band can exploit propagation modes other than line‐of‐sight and are hence widely employed to provide over‐the‐horizon surveillance and remote sensing. Most HF radars operating today rely on surface wave propagation; while opportunities for enhancing their performance by adding cognitive features exist, these have not been widely seized. In contrast, designers of HF skywave radars, which exploit ionospheric reflection to achieve ranges in excess of 4000 km, have long sought to counter the enormous challenges of the geophysical environment by implementing schemes to raise radar intelligence quotient (IQ) and autonomy. Measures that have been explored relate to resource allocation, operating procedures, signal processing, target classification and remote sensing. The perception–action cycle constitutes the structural element of these developments, accessing prior knowledge and input from auxiliary sensors, exactly as proposed by those who later coined the term cognitive radar . Here, the roles of cognition in HF skywave radars are reviewed, illustrating the needs and benefits with examples including detection in sea clutter, ionospheric channel compensation and multiple‐input and multiple‐output HF radar.